Astragalus polysaccharides protect against Di-n-butyl phthalate-induced testicular damage by modulating oxidative stress, apoptosis, and the PI3K/Akt/mTOR pathway in rats - Bakeer, Manal R.; Soliman, Seham Samir; Ahmed, Omaima; Youssef, Fady Sayed; Ali, Ghada E.; Aljarba, Nada H.; Zouganelis, George D.; Rashad, Maha M. (Frontiers in Veterinary Science, 2025)
IntroductionDi-n-butyl phthalate (DBP), a common plasticizer, is associated with oxidative stress and male reproductive toxicity. Astragalus polysaccharides (APS) have known antioxidative and anti-inflammatory properties, but their role in male reproductive health has not been fully elucidated.MethodsTwenty-four male rats were randomly assigned to four groups (n = 6 each): control, DBP-only (500 mg/kg/day), APS-only (200 mg/kg/day), and APS + DBP (500 mg/kg/day DBP + 200 mg/kg/day APS). Treatments were administered orally for 8 weeks. Biochemical, histological, and molecular analyses were conducted to evaluate testicular function, oxidative stress markers, and gene expression.ResultsDBP exposure significantly decreased serum testosterone levels, catalase (CAT) activity, lactate dehydrogenase (LDH) activity, and sperm quality, while increasing malondialdehyde (MDA) levels and apoptotic markers Casp3, Casp9. APS co-treatment significantly restored antioxidant enzyme activity, improved sperm parameters, reduced MDA levels, and alleviated histopathological damage. Gene expression analysis revealed upregulation of Nrf2 and SOD, and modulation of the PI3K/AKT/mTOR signaling pathway.DiscussionAPS exerts protective effects against DBP-induced testicular damage by enhancing antioxidant defenses and regulating key molecular pathways. These findings highlight the therapeutic potential of APS in preventing male infertility associated with environmental toxicants.